Post-deposition ageing reactions of plasma derived polyterpenol thin films - Bazaka, Kateryna; Jacob, Mohan V. (Polymer degradation and stability, 2010)
Owing to the structural flexibility, uncomplicated processing and manufacturing capabilities, plasma polymers are the subject of active academic as well as industrial research. Polymer thin films prepared from non-synthetic monomers combine desirable optical and physical properties with biocompatibility and environmental sustainability. However, the ultimate expediency and implementation of such materials will dependent on the stability of these properties under varied environmental conditions. Polyterpenol thin films were manufactured at different deposition powers. Under ambient conditions, the bulk of ageing occurred within first 150 h after deposition and was attributed to oxidation and volumetric relaxation. Films observed for further 12 months showed no significant changes in thickness or refractive index. Thermal degradation behaviour indicated thermal stability increased for the films manufactured at higher RF powers. Annealing the films to 405 °C resulted in full degradation, with retention between 0.29 and 0.99%, indicating films' potential as sacrificial material.